Streptomyces rugosispiralis sp. nov., a Novel Actinobacterium Isolated from Peat Swamp Forest Soil That Produces Ansamycin Derivatives and Nocardamines - Trinset Weeraphan; Khomsan Supong; Paranee Sripreechasak; Rumpa Jutakanoke; Supalerk Kowinthanaphat; Somboon Tanasupawat; Pattama Pittayakhajonwut; Wongsakorn Phongsopitanun (MDPI AG, 2023)
Actinomycetes, especially the genus Streptomyces, are one of the most promising sources of bioactive natural products. In this study, a novel Streptomyces strain, RCU-064T, was isolated from a soil sample collected from a peat swamp forest in Thailand. Strain RCU-064T showed the highest 16S rRNA gene sequence similarity (99.06%) with Streptomyces malaysiensis NBRC 16446T. Based on a polyphasic approach, strain RCU-064T represents a novel species of the genus Streptomyces, for which the name Streptomyces rugosispiralis sp. nov. is proposed. The chemical isolation of the crude ethyl acetate extracts of the strain led to the isolation of six compounds: (1) geldanamycin, (2) 17-O-demethylgeldanamycin, (3) reblastatin, (4) 17-demethoxyreblastatin, (5) nocardamine, and (6) dehydroxynocardamine. These compounds were evaluated for their biological activities. All compounds showed no antimicrobial activity against tested microorganisms used in this study. Compounds (1)-(4) displayed cytotoxic activity against the NCI-H187 cell line, with IC50 values ranging from 0.045-4.250 µg/mL. Cytotoxicity against the MCF-7 cell line was found in compounds (1) and (3) with IC50 values of 3.51 and 1.27 µg/mL, respectively. Compounds (5) and (6) exhibited cytotoxicity only against Vero cells (IC50 of 16.57 µg/mL) and NCI-H187 cells (IC50 of 13.96 µg/mL), respectively. These results indicate that peat swamp forest soil remains a promising reservoir of novel actinomycetes capable of producing bioactive natural products.